Exploring Students’ Response Of Applying GBA In Creative Writing: An Action Research - Helena, Chika; Pujiawati, Nia; Rahmawati, Maya (Jurnal Ilmiah Wahana Pendidikan, 2024)
Writing considered as one of the language skills that learners need to acquires as it is an important ability for them to fulfilled their role as a student. While prior research focused on GBA in analyzing academic writing, this study bridges the methodological void by exploring the student’s responses to its implementation in creative writing contexts. This study used action research involving six students in the eight-grade of a private senior high school. Data was collected through observation, interviews, and students’ documents. Positive responses, increased motivation, and transformed perspectives on writing emerged as key outcomes.